Brief Report: Misinterpretation of Coculture Differentiation Experiments by Unintended Labeling of Cardiomyocytes Through Secondary Transduction: Delusions and Solutions123. (27th November 2012) - Ramkisoensing, Arti A.; De Vries, Antoine A. F.; Schalij, Martin J.; Atsma, Douwe E.; Pijnappels, Daniël A.
Abstract: Cardiomyogenic differentiation of stem cells can be accomplished by coculture with cardiomyocytes (CMCs). To facilitate their identification, stem cells are often labeled through viral transduction with a fluorescent protein. A second marker to distinguish stem cell‐derived CMCs from native CMCs is rarely used. This study aimed to investigate the occurrence of secondary transduction of unlabeled neonatal rat (nr) CMCs after coculture with human cells that had been transduced 0, 7, or 14 days earlier with a vesicular stomatitis virus (VSV) G protein‐pseudotyped lentiviral vector (LV) encoding enhanced green fluorescent protein (GFP). To reduce secondary LV transfer, GFP‐labeled cells were incubated with non‐heat‐inactivated human serum (NHI) or with VSV‐neutralizing rabbit serum (αVSV). Heat‐inactivated human serum and normal rabbit serum were used as controls. Immunostaining showed substantial GFP gene transfer to nrCMCs in cocultures started at the day of transduction indicated by the presence of GFP‐positive/human lamin A/C‐negative nrCMCs. The extent of secondary transduction was significantly reduced in cocultures initiated 7 days after GFP transduction, while it was completely abolished when human cells were added to nrCMCs 14 days post‐transduction. Both NHI and αVSV significantly reduced the occurrence of secondary transduction compared to their controls. However, under all circumstances, GFP‐labeled human cells had to be passaged for 14 days prior to coculture initiation to prevent any horizontal GFP gene transfer to the nrCMCs. This study emphasizes that differentiation experiments involving the use of viral vector‐marked donor cells should be interpreted with caution and describes measures to reduce/prevent secondary transduction. STEM CELLS 2012;30:2830–2834